Biopolitica ed ecologia L'epistemologia politica del discorso biologico tra Michel Foucault e Georges Canguilhem - Angelini, Andrea (Premio Ricerca «Città di Firenze», 2021)
One of the core issues in Michel Foucault's and Georges Canguilhem's works is the study of the epistemological status and political functioning of biological discourse, explored in its fully heterogeneous, plural, and conflictual character. Starting from the relations and tensions between their theoretical orientations, the present work attempts a critical re-reading of their researchs, with the aim of integrating and mobilizing their analysis in light of contemporary political and epistemological debates. In this respect, Canguilhem's biological philosophy allows us to re-examine the foucauldian conceptions of history, society, subjectivity, technology, and environment; moreover, it enables a re-questioning about the spaces of intervention of biopolitical technologies from a socio-ecological and eco-historical perspective.